Mental Health Outcomes Among British Healthcare Workers—Lessons From the First Wave of the Covid-19 Pandemic. Issue 8 (9th August 2021) - Debski, Maciej; Abdelaziz, Hesham K.; Sanderson, Jo; Wild, Susan; Assaf, Omar; Wiper, Andrew; Nabi, Amjad; Abdelrahman, Amr; Eichhofer, Jonas; Skailes, Geraldine; Gardner, Jim; Moynes, Kevin; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To ascertain the level of psychological distress, using validated psychology tools, among British National healthcare workers (HCW) during the first wave of the Covid-19 crisis. Methods: A multi-centre, anonymized, all-comer staff survey across 3 hospitals in Lancashire, England during the Covid-19 first wave (April to June 2020), consisting of Patient Health Questionnaire (PHQ-9), Perceived Stress Scale-10 (PSS-10), Generalized Anxiety Disorder-7 (GAD-7), and Impact of Events Scale (IES-6). Results: Among 1113 HCW, median (IQR) PHQ-9, GAD-7, PSS-10, and IES-6 score was 7 (3 to 11), 6 (3 to 11), 19 (13 to 24), and 9 (5 to 14), respectively. Potential predictors of higher levels of psychological distress included living alone, disabled dependents, history of depression/anxiety, and being female. Conclusions: The study indicates a high prevalence of psychological distress during the acute Covid-19 period among HCW, identifies groups at risk and areas of future research.